A Review of Location Prediction Techniques in Mobile Ad Hoc Networks - M. Zaki, Salim; Ngadi, M. A.; Maznah Kamat; A. Razak, Shukor (Al-Qadisiyah Journal of Pure Science, 2020)
Predicting future locations of mobile objects has received a lot of attention in research due to its importance in mobile ad hoc networks. The precise location of a mobile node is essential in determining the location of the destination node for the purpose of communication. High mobility of nodes and delay in sending current location affect the accuracy of mobile nodes’ locations. Providing accurate location needs well-designed location prediction technique considers a number of factors that assist in retrieving up-to-date locations. This paper reviews available models: mathematical models and models with neural network and address the problems in location prediction techniques and provides a deep analysis of the good features for improved prediction techniques.